Receptores celulares, interferón y apoptosis en la resistencia natural a las infecciones virales (2000)
ABSTRACT: Some vertebrate hosts have the capacity to counteract viral infections by means so called mechanisms of natural resistance against viral infections. These mechanisms make part of the innate or acquired immunity and include processes like apoptosis, virus-receptor interactions, synthesis of molecules such as interferon and nitric oxide and other mechanisms mediated by the MHC phenotype or the capacity of natural killer cells to recognize the infected cell. In this review we will discuss host resistance to viral infections through apoptosis, interferon and viral-receptor interactions.